Changes in skin score in early diffuse cutaneous systemic sclerosis are associated with changes in global disease severity. (29th July 2019) - Zheng, Boyang; Nevskaya, Tatiana; Baxter, Carl A; Ramey, Dena R; Pope, Janet E; Baron, Murray; ,
Abstract: Objective: To determine whether skin score changes are associated with changes in overall disease severity, function and quality of life in early dcSSc patients. Methods: A total of 154 and 128 dcSSc patients from the Canadian Scleroderma Research Group database with 1 and 2 year follow-up and a disease duration ⩽5 years without end-stage organ damage and/or significant comorbidity at the initial visit were included. Skin was assessed using the modified Rodnan skin score (mRSS) and disease severity by the summed Medsger disease severity score (DSS) (without skin domain), physician and patient global assessments, function [HAQ disability index (HAQ-DI)] and quality of life [36-item Short Form Health Survey (SF-36) physical component summary (PCS)]. Analyses were repeated in patients with a disease duration ⩽3 years. Results: At 2 years, 64 (50%) patients had improved skin (mRSS decrease of ⩾5 points and/or ⩾25%). Skin improvers had improved summed DSS ( P = 0.002); better physician global assessments of disease activity, severity and damage (all P ⩽ 0.003); better HAQ-DI ( P = 0.001) and SF-36 PCS ( P = 0.005). Changes in the mRSS were positively correlated with changes in summed DSS ( P = 0.006) and other disease outcomes. In the 26 (20.3%) patients with worsened skin (mRSS increase of ⩾5 points and/or ⩾25%), the summed DSS and physician global assessments were worse ( P = 0.01 and P ⩽ 0.009, respectively). In the subgroup with a disease duration ⩽3 years, similar associations were found. Conclusion: At 1 and 2 years, overall disease improvement parallels skin improvement in early dcSSc. This is important for prognosis and reflects the value of mRSS as an outcome measure in trials with these patients.